Using Multimodal Functional Imaging in the Management of SDHx-Related Pheochromocytoma and Paraganglioma - White, Gemma (J Endocr Soc, 2021)
Background: Succinate Dehydrogenase (SDH) subunit pathogenic variants predispose to Pheochromocytoma and Paraganglioma (PPGL). Functional imaging harnesses the innate receptor expression and the aberrant cellular pathways in PPGLs to improve diagnostic accuracy & guide treatments, including nuclear medicine therapies. Currently commonly available functional imaging modalities include (18)F-FDG PET, (123)I-MIBG and (68)Ga-DOTATATE. Aims: To analyze the use of (123)I-MIBG, (18)F-FDG PET and (68)Ga-DOTATATE in patients harboring SDHB & SDHD pathogenic variants and determine the detection rates for both primary tumors and metastatic sites of disease. Methods: Retrospective review of patient records and imaging reports allowed tumor characteristics and imaging features of 21 patients with SDH-related PPGL to be recorded. Contrast enhanced CT/MRI were used as control to calculate the sensitivity of each functional imaging modality. Avidity of the primary lesion and metastatic deposits were used to calculate detection rates. (123)I-MIBG imaging was available for 22 primary tumors (8 SDHB, 14 SDHD), (18)FDG-PET for 24 (9 SDHB, 15 SDHD) and (68)Ga-DOTATATE for 6 (2 SDHB, 4 SDHD) respectively. Results: 29 PPGLs (primary and metastases, 13 SDHB, 16 SDHD) were identified in 21 patients. (123)I-MIBG detected 14/22 (64%) primary tumors; 5/8 (63%) SDHB and 9/14 (64%) SDHD-related PPGL. According to tumor location, 3/3 PCCs, 6/8 HNPGLs and 4/11 non-HNPGLs demonstrated (123)I-MIBG avidity. Both(18)F-FDG PET and (68)Ga-DOTATATE detected all PPGLs imaged; 24 (9 SDHB, 15 SDHD) and 6 (2 SDHB, 4 SDHD) respectively, demonstrating 100% sensitivity in the detection of the primary PPGL in all the above locations. 6 metastatic deposits (located in bone, lungs, liver and local lymph nodes) in 4 patients were imaged using all 3 modalities (3 SDHB, 1 SDHD), all of which were avid on (18)F-FDG PET and (68)Ga-DOTATATE whereas only 50% demonstrated avidity on (123)I-MIBG imaging. Discussion: Recent guidelines promote preferential use of (68)Ga-DOTATATE and (18)F-FDG PET as initial functional imaging modalities in SDHx-related disease over (123)I-MIBG. The results from our patient cohort indicate superior sensitivity (100%) for detection of SDHx-related disease with FDG and Dotatate compared with MIBG. In contrast to the current literature, a high proportion (75%) of HNPGLs in our series demonstrated MIBG avidity. Further prospective studies are needed to further evaluate these and various other novel tracers to inform diagnostic and therapeutic strategy in PPGLs arising from SDHx and various other germline and somatic pathogenic variants.